Randomized phase 2 study of carboplatin and bevacizumab in recurrent glioblastoma. Issue 11 (30th June 2015) - Field, Kathryn M.; Simes, John; Nowak, Anna K.; Cher, Lawrence; Wheeler, Helen; Hovey, Elizabeth J.; Brown, Christopher S.B.; Barnes, Elizabeth H.; Sawkins, Kate; Livingstone, Ann; Freilich, Ron; Phal, Pramit M.; et al.
Abstract: Background: The optimal use of bevacizumab in recurrent glioblastoma (GBM), including the choice of monotherapy or combination therapy, remains uncertain. The purpose of this study was to compare combination therapy with bevacizumab monotherapy. Methods: This was a 2-part randomized phase 2 study. Eligibility criteria included recurrent GBM after radiotherapy and temozolomide, no other chemotherapy for GBM, and Eastern Cooperative Oncology Group performance status 0–2. The primary objective (Part 1) was to determine the effect of bevacizumab plus carboplatin versus bevacizumab monotherapy on progression-free survival (PFS) using modified Response Assessment in Neuro-Oncology criteria. Bevacizumab was given every 2 weeks, 10 mg/kg; and carboplatin every 4 weeks, (AUC 5). On progression, patients able to continue were randomized to continue or cease bevacizumab (Part 2). Secondary endpoints included objective radiological response rate (ORR), quality of life, toxicity, and overall survival (OS). Results: One hundred twenty-two patients (median age, 55y) were enrolled to Part 1 from 18 Australian sites. Median follow-up was 32 months, and median on-treatment time was 3.3 months. Median PFS was 3.5 months for each arm (hazard ratio [HR]: 0.92, 95% CI: 0.64–1.33, P = .66). ORR was 14% (combination) versus 6% (monotherapy) ( P = .18). Median OS was 6.9 (combination) versus 7.5 months (monotherapy) (HR: 1.18, 95% CI: 0.82–1.69, P = .38). The incidence of bevacizumab-related adverse events was similar to prior literature, with no new toxicity signals. Toxicities were higher in the combination arm. Part 2 data ( n = 48) will be reported separately. Conclusions: Adding carboplatin resulted in more toxicity without additional clinical benefit. Clinical outcomes in patients with recurrent GBM treated with bevacizumab were inferior to those in previously reported studies. Clinical trials registration nr: ACTRN12610000915055.